Preparation and characterization of blends of poly (ethylene oxide) and monocarboxylic acid modified epoxidized natural rubber / Wan Nurhidayah A Karim - Wan Nurhidayah, A Karim (2017)
By reacting and a higher value has Tg value of In addition, t also This dissertation describes a study of using benzoic acid and acetic acid to fully ring-opened ENR50, which is natural rubber with 50% of the isoprene units epoxidized. ENR50 was chemically modified by ring opening the epoxide groups to produce a new chemically modified rubber. The reaction was carried out between the ENR50 dissolved in toluene with excess carboxylic acids (acetic acid and benzoic acid) at 105C.Ring-opening of epoxide group by the carboxylic acids has led to an increase in the Tg due to the formation of polar –OH after ester groups, and the structural changes could be observed in the infra-red spectra (FTIR) and nuclear magnetic resonance (NMR). Changes in thermal properties were measured with thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC). The initial ENR50 has a Tgof -29oC and the acetic acid modified sample (Ac-ENR50) has led to a new Tg of 20oC while benzoic acid modified sample (Bz-ENR50) 12.3oC.The effects of blend ratio of the modified rubber and poly(ethylene oxide) (PEO) in the presence of 2%dopantlithium perchlorate(LiClO4) were investigated. FTIR results showed that there was no reaction between the Ac-ENR50/PEO/LiClO4 and Bz-ENR50/PEO/LiClO4 blends. The Bz-ENR50/PEO/LiClO4blends with the ratio at 30/70/2 have the highest value conductivity of 5.80X 10-7 S cm-1. Morphologicalstudies of the blends were carried out by polarizing optical microscopy (POM) and results further confirmed the immiscibility of the two polymers. The spherulites could not be seen for the blends containing Bz-ENR50/PEO/LiClO4higher than 50/50/2. Fibrillary fine texture of the spherulites of PEO was clearly observed at higher PEO content in the blends. This dissertation describes a study of using benzoic acid and acetic acid to fully ring-opened ENR50, which is natural rubber with 50% of the isoprene units epoxidized. ENR50 was chemically modified by ring opening the epoxide groups to produce a new chemically modified rubber. The reaction was carried out between the ENR50 dissolved in toluene with excess carboxylic acids (acetic acid and benzoic acid) at 105C.Ring-opening of epoxide group by the carboxylic acids has led to an increase in the Tg due to the formation of polar –OH after ester groups, and the structural changes could be observed in the infra-red spectra (FTIR) and nuclear magnetic resonance (NMR). Changes in thermal properties were measured with thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC). The initial ENR50 has a Tg of -29oC and the acetic acid modified sample (Ac-ENR50) has led to a new Tg of 20oC while benzoic acid modified sample (Bz-ENR50) 12.3oC.The effects of blend ratio of the modified rubber and poly(ethylene oxide) (PEO) in the presence of 2%dopantlithium perchlorate(LiClO4) were investigated. FTIR results showed that there was no reaction between the Ac-ENR50/PEO/LiClO4 and Bz-ENR50/PEO/LiClO4 blends. The Bz-ENR50/PEO/LiClO4blends with the ratio at 30/70/2 have the highest value conductivity of 5.80X 10-7 S cm-1. Morphologicalstudies of the blends were carried out by polarizing optical microscopy (POM) and results further confirmed the immiscibility of the two polymers. The spherulites could not be seen for the blends containing Bz-ENR50/PEO/LiClO4higher than 50/50/2. Fibrillary fine texture of the spherulites of PEO was clearly observed at higher PEO content in the blends.